Análise dos resultados da aplicação de ferramenta de Benchmarking financeiro em empresas do setor de construção civil do Estado do Ceará - Rocha, Yuri Braga da (2018)
The use of benchmarking has been increasingly important for the competitiveness of companies in the current market. Benchmarking enables companies to monitor their competitors' practices and financial situations, thereby informing its decision-making in order to increase its competitiveness and improve its market position. The present study aims to apply the financial benchmarking tool developed by Baltazar (2015) in Ceará civil construction companies, analyze their results from a qualitative and statistical point of view and compare these results with data from other sectors previously analyzed. This study is classified as an applied research, quantitative and descriptive, uses the concepts of bibliographic research and applied study to treat the subject. The data needed to carry out this research were collected in the balance sheets of companies published in the Official Gazettes of the State of Ceará. The data collected were analyzed and treated so that the results were consistent with reality. After the treatment, the data obtained were used to calculate the performance indicators of the SIMAP Competitivo benchmarking tool. These indicators were then compared with indicators from other companies in the SIMAP Competitivo database. The results of the study demonstrate the validity of the tool used, since they are consistent between economic sectors and different locations. It suggests then that the financial benchmarking tool can be used more comprehensively.